Desensitization using imlifidase and EndoS enables chimerism induction in allosensitized recipient mice. Issue 9 (7th April 2020) - Lin, Jiaxin; Boon, Louis; Bockermann, Robert; Robertson, Anna‐Karin; Kjellman, Christian; Anderson, Colin C.
Abstract : Mixed hematopoietic chimerism induction as a way to foster tolerance to donor organs in recipients who have been sensitized to donor antigens is challenging. Donor‐specific antibodies (DSA) are a dominant barrier toward successful donor bone marrow engraftment. Although desensitization methods are routinely used in recipients with allosensitization for allogeneic bone marrow transplantation, engraftment is frequently unsuccessful. To overcome the barrier of prior sensitization we tested enzymatic desensitization of donor‐specific IgG using imlifidase and endoglycosidase of Streptococcus pyogenes (EndoS), which both partially block the function of DSA in mice, as a novel approach to improve murine bone marrow engraftment in primed hosts. We found that EndoS was capable of inhibiting antibody‐mediated killing of donor cells in vivo. Furthermore, the effect of EndoS depended on the titer of DSA and the genetic background of the recipients. In combination with imlifidase, EndoS improved the survival of donor bone marrow cells. Together with cyclophosphamide, bortezomib, T cell depletion, and nonlethal irradiation, imlifidase in combination with EndoS allowed allogeneic bone marrow engraftment in sensitized recipients. We conclude that enzymatic inactivation of DSA, using the combination of imlifidase and EndoS, can be used for inducing donor hematopoietic chimerism in allosensitized recipient mice in combination with other desensitization strategies. Abstract : Imlifidase and EndoS overcome the barrier of donor‐specific antibody, facilitating the achievement of hematopoietic chimerism in a mouse model of bone marrow transplantation.